Changes in the emotional intelligence of occupational therapy students during practice education: A longitudinal study. (July 2018) - Gribble, Nigel; Ladyshewsky, Richard K; Parsons, Richard
Introduction: Emotional intelligence competencies assist occupational therapists in responding in a manner that enables them to be effective healthcare practitioners. Method: This longitudinal study tracked the emotional intelligence of occupational therapy and business students using the Emotional Quotient Inventory 2.0 at three time-points over the final 16 months of their university programme. Results: Undergraduate occupational therapy students ( n = 139 at time-point 1; n = 52 at time-point 3) completed a mean of 117 days of practice education. Before occupational therapy students commenced placements, emotional intelligence scores were significantly lower than population norms in self-regard, self-expression, assertiveness, independence, problem-solving, stress management, stress tolerance and flexibility. By the end of their programme, students reported significant increases in the emotional intelligence realms of total emotional intelligence score, self-perception, decision-making, self-actualisation, emotional self-awareness, independence and reality testing. However, assertiveness, problem-solving and stress tolerance remained relatively low, and other emotional intelligence domains remained below the population norms. The business students who did zero practice placements showed no increase in any emotional intelligence domains over the same period. Conclusion: Emotional intelligence skills are malleable and can improve during practice placements. Supervisors and employers should encourage students and new graduates to practice their emotional intelligence skills under supervision and then provide feedback, so they are better prepared for the emotional demands of healthcare workplaces.